2023
DOI: 10.1093/nar/gkad159
|View full text |Cite
|
Sign up to set email alerts
|

RNA binding proteins Smaug and Cup induce CCR4–NOT-dependent deadenylation of the nanos mRNA in a reconstituted system

Abstract: Posttranscriptional regulation of the maternal nanos mRNA is essential for the development of the anterior – posterior axis of the Drosophila embryo. The nanos RNA is regulated by the protein Smaug, which binds to Smaug recognition elements (SREs) in the nanos 3’-UTR and nucleates the assembly of a larger repressor complex including the eIF4E-T paralog Cup and five additional proteins. The Smaug-dependent complex represses translation of nanos and induces its deadenylation by the CCR4–NOT deadenylase. Here we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…Whether MARF1 or Smaug directly associates with the CCR4-NOT complex was unknown. Using ReLo, we found that Smaug interacts with the NOT3 subunit 63 and that MARF1 binds to the NOT1 subunit (Fig. 4e and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Whether MARF1 or Smaug directly associates with the CCR4-NOT complex was unknown. Using ReLo, we found that Smaug interacts with the NOT3 subunit 63 and that MARF1 binds to the NOT1 subunit (Fig. 4e and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Interaction data for Bruno and Cup are shown in Supplementary Fig. 7 and data for Smaug are published in 63 . b Bam interacted with CAF40.…”
Section: Resultsmentioning
confidence: 99%
“…Given the large number of regulated mRNAs, it is not surprising that expression of Nos protein is tightly controlled. During oogenesis and embryogenesis, much of this control is exerted via the 3’-UTR of its mRNA to control the timing and location of protein accumulation (Forrest et al, 2004; Pekovic et al, 2023; Peng & Gavis, 2022); we therefore intentionally designed all of the transgenes used in this work to express mRNAs bearing the native nos 3’-UTR. Our results suggest an additional level of control–– negative autoregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The trans-acting factors recruited by these sequence elements typically induce mRNA degradation via deadenylation coupled to the 5′-3′ degradation pathway ( Muhlrad et al, 1994 ; Stoecklin et al, 2006 ; Bonisch et al, 2007 ). Well-characterised examples include the A/U-rich element (ARE) ( Stoecklin et al, 2006 ), microRNA binding sites ( Behm-Ansmant et al, 2006 ; Piao et al, 2010 ), and sequence elements recognised by developmental regulators such as Smaug and Bicaudal-C ( Zaessinger et al, 2006 ; Chicoine et al, 2007 ; Pekovic et al, 2023 ). In addition to recruitment by mRNA-specific factors, the 5′-3′ degradation pathway can be induced by general mechanisms involving the interaction between the cytoplasmic poly(A)-binding protein (PABPC) 1 and members of the BTG/Tob family of proteins, which include TOB1 and its paralogue TOB2, and the BTG1 and BTG2 paralogues that are frequently mutated in non-Hodgkin lymphoma ( Mauxion et al, 2009 ; Winkler, 2010 ; Yuniati et al, 2018 ; Almasmoum et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%